Los estilos de apego y el consumo de sustancias psicoactivas en adolescentes - León Fernández, Fernando José (2024)
The consumption of psychoactive substances turns out to be a public health problem. and a common risk behavior in adolescents; if it’s not modified, it could possibly lead to addiction. Attachment style is the pattern of interpersonal relationship that emerges when one person establishes contact with another; it is based on mental representations of oneself, others, and the bond. The objective of the research is to identify the relationship between attachment styles and the consumption of psychoactive substances in adolescents. A search was carried out in databases to obtain research involving these variables and studies that met the inclusion-exclusion criteria (n=10) were selected using the PRISMA guide. It was found that there is a relationship between attachment styles and substance consumption in adolescents, in addition, it was evidenced that different attachment styles can be a protective or risk factor towards substance consumption and addiction. No research was found applied to the Peruvian context, this highlights the importance of replicating this research in the Peruvian reality.